The Impact of Variable Inlet Mixture Stratification on Flame Topology and Emissions Performance of a Premixer/Swirl Burner Configuration. (11th October 2012) - Koutmos, P.; Paterakis, G.; Dogkas, E.; Karagiannaki, Ch.
Abstract : The work presents the assessment of a low emissions premixer/swirl burner configuration utilizing lean stratified fuel preparation. An axisymmetric, single- or double-cavity premixer, formed along one, two, or three concentric disks promotes propane-air premixing and supplies the combustion zone at the afterbody disk recirculation with a radial equivalence ratio gradient. The burner assemblies are operated with a swirl co-flow to study the interaction of the recirculating stratified flame with the surrounding swirl. A number of lean and ultra-lean flames operated either with a plane disk stabilizer or with one or two premixing cavity arrangements were evaluated over a range of inlet mixture conditions. The influence of the variation of the imposed swirl was studied for constant fuel injections. Measurements of turbulent velocities, temperatures, OH* chemiluminescence and gas analysis provided information on the performance of each burner set up. Comparisons with Large Eddy Simulations, performed with an 11-step global chemistry, illustrated the flame front interaction with the vortex formation region under the influence of the variable inlet mixture stratifications. The combined effort contributed to the identification of optimum configurations in terms of fuel consumption and pollutants emissions and to the delineation of important controlling parameters and limiting fuel-air mixing conditions.